Continuous monitoring of elastic modulus of mortars using a single-board computer and cost-effective components - Russo, Thomas Vincent Jacques (2023)
The Elastic Modulus Measurement through Ambient Response Method (EMM-ARM) is designed to continuously monitor the elastic modulus of hardening construction materials such as concrete, cement paste, mortars, stabilized soils, and epoxy resin. In practice, a composite beam, made of the tested material in its mould, is induced to vibration by means of environmental or controlled excitation, and its resonant frequency is identified. The material’s elastic modulus can then be calculated based on the vibration equation of structural systems. The traditional system to conduct EMM-ARM experiments is based on specialized equipment and on proprietary licensed software, which results in a considerable cost, as well as limited options for customization. The paper hereby presented proposes a delve into the development and validation of a cost-effective and open-source system that is able to conduct EMM-ARM experiments. By using a Raspberry Pi for the computing device and cost-effective electronic components, the cost of the system was one-twentieth of the traditional one, without compromising the measurement reliability. The composite beam’s excitation is generated, while the vibration response is recorded by the proposed system simultaneously, since the Raspberry Pi supports multiprocessing programming techniques. The flexibility earned by the exclusive use of open-source and cost-effective resources creates countless application possibilities for the proposed system.